Comparison of Hydrogen Peroxide Secretion From Living Cells Cultured in Different Formats Using Hydrogel-Based LSPR Substrates - Siao, Yang-Jyun; Peng, Chien-Chung; Tung, Yi-Chung; Chen, Yih-Fan (Frontiers in Bioengineering and Biotechnology, 2022)
Reactive oxygen species (ROS), a number of reactive molecules and free radicals derived from molecular oxygen, are generated as by-products during mitochondrial electron transport within cells. Physiologically, cells are capable of metabolizing the ROS exploiting specific mechanisms. However, if excessive ROS accumulate inside the cells, it will cause the cells apoptosis or necrosis. Hydrogen peroxide (H2O2) is one of the essential ROS often participating in chemical reactions in organisms and regulating homeostasis in the body. Therefore, rapid and sensitive detection of H2O2 is a significant task in cell biology research. Furthermore, it has been found that cells cultured in different formats can result in different cellular responses and biological activities. In order to investigate the H2O2 secretion from the cells cultured in different formats, a hydrogel-based substrate is exploited to separate relatively large molecular (e.g., proteins) for direct measurement of H2O2 secreted from living cells in complete cell culture medium containing serum. The substrate takes advantage of the localized surface plasmon resonance (LSPR) method based on enzyme immunoprecipitation. In addition, the H2O2 secreted from the cells cultured in different dimensions (suspension of single cells and three-dimensional cell spheroids) treated with identical drugs is measured and compared. The spheroid samples can be prepared with ample amount using a designed microfluidic device with precise control of size. The results show that the H2O2 secretion from the cells are great affected by their culture formats.